2014
DOI: 10.1111/mpp.12156
|View full text |Cite
|
Sign up to set email alerts
|

Fungal cellulase is an elicitor but its enzymatic activity is not required for its elicitor activity

Abstract: Plant-pathogenic fungi produce cellulases. However, little information is available on cellulase as an elicitor in plant-pathogen interactions. Here, an endocellulase (EG1) was isolated from Rhizoctonia solani. It contains a putative protein of 227 amino acids with a signal peptide and a family-45 glycosyl hydrolase domain. Its aspartic acid (Asp) residue at position 32 was changed to alanine (Ala), resulting in full loss of its catalytic activity. Wild-type and mutated forms of the endoglucanase were expresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 60 publications
2
45
0
1
Order By: Relevance
“…The cells were lysed by freezing and thawing, followed by sonication, and the recombinant protein was purified with elution buffer (column buffer supplemented with 10 mM maltose) on a 5-ml amylose column MBPTrap TM HP (GE Healthcare Life Sciences, Issaquah, WA, USA). Enzyme activities were measured as described previously using CMC (C4888; Sigma, St. Louis, MO, USA) as the substrate (Ma et al, 2015a).…”
Section: Recombinant Protein Purification and Enzyme Activity Assaysmentioning
confidence: 99%
See 2 more Smart Citations
“…The cells were lysed by freezing and thawing, followed by sonication, and the recombinant protein was purified with elution buffer (column buffer supplemented with 10 mM maltose) on a 5-ml amylose column MBPTrap TM HP (GE Healthcare Life Sciences, Issaquah, WA, USA). Enzyme activities were measured as described previously using CMC (C4888; Sigma, St. Louis, MO, USA) as the substrate (Ma et al, 2015a).…”
Section: Recombinant Protein Purification and Enzyme Activity Assaysmentioning
confidence: 99%
“…The elicitor activity was detected by infiltration of recombinant wild-type and mutant proteins in N. benthamiana; the VdNLP1 and MBP were used as positive and negative controls respectively. Cytosolic Ca 21 was measured using the Ca 21 -sensitive fluorescent dye Fluo-4 acetoxymethyl ester (Fluo 4-AM) as described previously (Ma et al, 2015a). Nicotiana tabacum L. cv.…”
Section: Elicitor Activity Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…For example, ethylene‐inducing xylanase from T . reesei and cellulase from Rhizoctonia solani have been shown to be inducers of host defence responses without the requirement of any enzymatic activity (Enkerli et al ., ; Ma et al ., ; Ron and Avni, ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that an endocellulase (EG1) isolated from Rhizoctonia solani contains a putative protein of 227 amino acids with a signal peptide and a family-45 glycosyl hydrolase domain. Its aspartic acid (Asp) residue at position 32 was changed to alanine (Ala), resulting in full loss of its catalytic activityhence the enzymatic activity of this endoglucanase is not required for its elicitor activity (Ma et al 2015).…”
Section: Proteinmentioning
confidence: 99%